2013
DOI: 10.1007/978-3-319-02414-1_17
|View full text |Cite
|
Sign up to set email alerts
|

End-to-End Service Quality for Cloud Applications

Abstract: This paper aims to highlight the importance of end-to-end service quality for cloud services, with a focus on telecom carrier-grade services. In multi-tenant distributed and virtualized cloud infrastructures, the enhanced level of resource sharing raises issues in terms of performance stability and reliability of cloud services, threatening the possibility to offer precise service levels in end-to-end scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…As a final remark, it is worth to mention that some of the toughest challenges in cloud computing are due to the need for providing SaaS offerings with stable and predictable service levels [53,89,64], through the interaction of the multitude of business players that may be involved, including multiple SaaS and IaaS providers and Network Service Providers. The establishment of proper SLA models among these players may be a challenge on its own, encompassing technological as well as business aspects that deserve attention in the future.…”
Section: Alternatives Not Based On Machine Virtualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a final remark, it is worth to mention that some of the toughest challenges in cloud computing are due to the need for providing SaaS offerings with stable and predictable service levels [53,89,64], through the interaction of the multitude of business players that may be involved, including multiple SaaS and IaaS providers and Network Service Providers. The establishment of proper SLA models among these players may be a challenge on its own, encompassing technological as well as business aspects that deserve attention in the future.…”
Section: Alternatives Not Based On Machine Virtualizationmentioning
confidence: 99%
“…In the telecommunication industry, there is a major shift from hardware-based provisioning of network functions to a softwarebased provisioning paradigm where virtualized network functions [94] are deployed in private or hybrid clouds of network operators [89]. For example, IP Multimedia Subsystem (IMS) components are traditionally designed and calibrated to run on specific hardware platforms with precise real-time and reliability requirements, given a target maximum workload specification, such as maximum number of supported subscribers or call attempts per second.…”
Section: Introductionmentioning
confidence: 99%
“…The application model may be associated with an endto-end latency constraint (not shown here for the sake of brevity), as described in our prior works [12], [21].…”
Section: A Application Modelsmentioning
confidence: 99%
“…NIST is also working in this area, with a series of reports being of value to the topic of end-to-end cloud service quality 3 , in addition to the well-known reports on the definition of cloud computing (Mell and Grance, 2011) and its reference architecture (Liu et al, 2011), where the importance of having cloud brokerage services is emphasized. Additional details on research and standardization efforts in this area can be found in (Oberle et al, 2013).…”
Section: Related Workmentioning
confidence: 99%
“…Even though recent standards and research efforts deal with predictable QoS levels in Cloud Computing (Oberle et al, 2013), spanning across different business and operations domains remains a great challenge. For example, a single user request may have to traverse access, metro, core and data center networks, and the top-down provisioning chain across the various cloud layers (SaaS, IaaS, etc.…”
Section: Introductionmentioning
confidence: 99%